Poema en 4 direcciones con hang drum = Tone poem with hang drum - Ma, Eve A.; Mann, Liron; Yamuza, Pilar; Palomino Productions ([Berkeley, California] : Palomino Productions, 2010)
Interweaving a hang-drum player with the story his music conjures up, we create a dream-like narrative of personal loss. By the end, the music and musician are overtaken and canceled out by the story. (NOTE: a hang drum is a percussion instrument that sounds like a cross between a xylophone and steel drums)--
Originally released as a motion picture in 2010
Starring: Liron Mann, Pilar Yamuza, Felicia German.
Cinematographer and editor, Eve A. Ma ; music, Liron Mann.
In Spanish; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 25, 2018)
Keywords: Experimental films; Short films; Documentary films; Nonfiction films; Internet videos; Streaming video